New and little known geophilomorph centipedes from Amazonian inundation forests near Manaus, Brazil (Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (1994)
A new genus is proposed within the family Geophilidae: Hyphydrophilus n. gen., for H. adisi n.sp. Four additional new species are described, i.e. the ballophilids Ityphilus crabilli n.sp. and Taeniolinum arbor urn n.sp. and the schendylids Pectiniunguis ascendens n.sp. and Schendylurus amazonicus n.sp. The geophilid species Ribautia centralis (SILVESTRI, 1907) is redescribed, after material from Brazil compared with the holotype. The ballophilid Thalthybius perrieri BRÓLEMANN, 1909 is transferred to the genus hyphilus COOK, 1889 and a lectotype is designated here for it.